(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Stunting is one of the problems currently being faced by Indonesia and has become a concern for the government because it is a serious condition in children which will eventually lead toaffect the quality of Indonesia’s young generation. Stunting is characterized by a child’s height below the average and a body that does not grow and develop properly according to his age which lasts for a long time. Even in the long term, stunting will eventually be followed by intelligence disorders in children due to lack of nutrition, including in Sumurwiru village, Cibeureum sub-district. This village, which has a population of 1164 people, has stunting problems, it can even be called a stunting emergency. This can be seen from the data obtained as many as 8 children experienced stunting even within a period of 6 months experiencing an increase in the stunting rate of 12 children. In addition, another problem in Sumurwiru village is the lack of food commodities as a source of fulfilling community nutrition which encourages stunting. Seeing this increase in numbers, the implementation of this catfish farming work program as a support for food self-sufficiency to fulfill nutrition in Sumurwiru village in preventing stunting through the Kelompok Wanita Tani (KWT) as the manager. This program also helps improve the economy of the Sumurwiru village community because catfish farming is a business that is in demand by farmers with a growing market value and a promising business. This activity consists of several stages as follows: 1) Field survey; 2) Coordination with managers of women farmer groups (KWT); 3) Cooperating with partners; 4) Program implementation; 5) Program evaluation.